2001
DOI: 10.3104/reports.111
|View full text |Cite
|
Sign up to set email alerts
|

Memory training for children with Down syndrome

Abstract: -One well-established fact concerning cognitive and language development in individuals with Down syndrome is that working memory is particularly poor, with auditory working memory worse than visual working memory. Working memory serves the functions of control, regulation, and active maintenance of information and is critical in daily complex cognitive activities. Thus, there is a strong need to fi nd effective and practical interventions targeted at improving working memory in individuals with Down syndrome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 43 publications
(41 reference statements)
2
18
0
1
Order By: Relevance
“…The research involved children with DS aged 6-14 years. In their findings and conclusions, Conners et al (2001) confirmed previous research findings that indicated that rehearsal training can enhance the working memory in individuals with DS. The use of technology can enhance working memory training.…”
Section: Technologies Used To Support Learning and The Potential Chalsupporting
confidence: 86%
See 2 more Smart Citations
“…The research involved children with DS aged 6-14 years. In their findings and conclusions, Conners et al (2001) confirmed previous research findings that indicated that rehearsal training can enhance the working memory in individuals with DS. The use of technology can enhance working memory training.…”
Section: Technologies Used To Support Learning and The Potential Chalsupporting
confidence: 86%
“…Bennett et al's (2013) findings above are supported by numerous other studies (Conners, Rosenquist & Taylor, 2001;Nadkarni, Sumi & Ashok, 2012). These authors argue that rehearsal training can improve the working memory in individuals with DS.…”
Section: Technologies Used To Support Learning and The Potential Chalmentioning
confidence: 80%
See 1 more Smart Citation
“…If this is the case, then one might be able to target interventions towards this problem, in the hope of improving rehearsal ineffi ciency. Indeed a number of studies have attempted to improve or train rehearsal in individuals with Down syndrome (Broadley & MacDonald, 1993;Broadley, MacDonald & Buckley, 1994;Comblain, 1994;Laws, MacDonald & Buckley, 1996;Laws, MacDonald, Buckley & Broadley, 1995; for more details on rehearsal training see Conners, Rosenquist and Taylor (2001).…”
Section: Discussionmentioning
confidence: 99%
“…If this is the case, then one might be able to target interventions towards this problem, in the hope of improving rehearsal ineffi ciency. Indeed a number of studies have attempted to improve or train rehearsal in individuals with Down syndrome (Broadley & MacDonald, 1993;Broadley, MacDonald & Buckley, 1994;Comblain, 1994;Laws, MacDonald & Buckley, 1996;Laws, MacDonald, Buckley & Broadley, 1995; for more details on rehearsal training see Conners, Rosenquist and Taylor (2001).The claim of a phonological loop defi cit in Down syndrome therefore has implications for our understanding of Down syndrome, and for possible intervention strategies. However, it is important to note that the accounts outlined above, although theoretically plausible, are not fully supported by empirical evidence.…”
mentioning
confidence: 99%